Asymmetric Synthesis of Protected Cyclohexenylamines and Cyclohexenols by Rhodium‐Catalyzed [2+2+2] Cycloaddition. (10th November 2016) - Masutomi, Koji; Sugiyama, Haruki; Uekusa, Hidehiro; Shibata, Yu; Tanaka, Ken
Abstract: It has been established that cationic rhodium(I)/axially chiral biaryl bis(phosphine) complexes catalyze the asymmetric [2+2+2] cycloaddition of 1, 6‐enynes with electron‐rich functionalized alkenes, enamides, and vinyl carboxylates, to produce the corresponding protected cyclohexenylamines and cyclohexenols. Interestingly, regioselectivity depends on structures of substrates. The present cycloaddition was successfully applied to the enantioselective total synthesis of (−)‐porosadienone by using the amide moiety as a leaving group.